2011
DOI: 10.1128/aac.01082-10
|View full text |Cite
|
Sign up to set email alerts
|

Herb-Drug Interaction between Echinacea purpurea and Darunavir-Ritonavir in HIV-Infected Patients

Abstract: The aim of this open-label, fixed-sequence study was to investigate the potential of Echinacea purpurea, a commonly used botanical supplement, to interact with the boosted protease inhibitor darunavir-ritonavir. Fifteen HIV-infected patients receiving antiretroviral therapy including darunavir-ritonavir (600/100 mg twice daily) for at least 4 weeks were included. E. purpurea root extract capsules were added to the antiretroviral treatment (500 mg every 6 h) from days 1 to 14. Darunavir concentrations in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Similar results were obtained in HIV-infected patients where Echinacea treatment, every 6 h for 28 days did not show an effect on C max and AUC (0-24) of etravirine (ClinicalTrials.gov:NCT01347658) [141], darunavir and ritonavir (ClinicalTrials.gov:NCT01046890) [142]. The limited number of patients included in the studies requires such results to be taken with great caution also in light of the fact that, after Echinacea treatment, individual patients did show a decrease in darunavir concentration at the end of the dosing interval (40%) and area under the time-concentration curve (30%) [142]. Moreover, additional experiments are clearly necessary to clarify whether or not Echinacea may inhibit intestinal CYP3A4 and induce hepatic CYP3A4 along with the identification of the active compounds and the underlying mechanisms.…”
Section: Echinaceasupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were obtained in HIV-infected patients where Echinacea treatment, every 6 h for 28 days did not show an effect on C max and AUC (0-24) of etravirine (ClinicalTrials.gov:NCT01347658) [141], darunavir and ritonavir (ClinicalTrials.gov:NCT01046890) [142]. The limited number of patients included in the studies requires such results to be taken with great caution also in light of the fact that, after Echinacea treatment, individual patients did show a decrease in darunavir concentration at the end of the dosing interval (40%) and area under the time-concentration curve (30%) [142]. Moreover, additional experiments are clearly necessary to clarify whether or not Echinacea may inhibit intestinal CYP3A4 and induce hepatic CYP3A4 along with the identification of the active compounds and the underlying mechanisms.…”
Section: Echinaceasupporting
confidence: 71%
“…More recently, Goey and colleagues [140] reported no changes in docetaxel AUC (0-∞) , t 1/2 and C max pre-and post-infusion values in cancer patients after treatment with Echinaforce ® three times daily for fourteen days [140]. Similar results were obtained in HIV-infected patients where Echinacea treatment, every 6 h for 28 days did not show an effect on C max and AUC (0-24) of etravirine (ClinicalTrials.gov:NCT01347658) [141], darunavir and ritonavir (ClinicalTrials.gov:NCT01046890) [142]. The limited number of patients included in the studies requires such results to be taken with great caution also in light of the fact that, after Echinacea treatment, individual patients did show a decrease in darunavir concentration at the end of the dosing interval (40%) and area under the time-concentration curve (30%) [142].…”
Section: Echinaceasupporting
confidence: 52%
“…99 In vitro, Echinacea , garlic, ginkgo biloba, ginseng, silymarin, and St John's wort have been shown to inhibit or induce enzymes or transporters involved in the metabolism or disposition of boceprevir and telaprevir. 99 In vivo , Echinacea 100,101 and silymarin 102,103 do not substantially alter HIV protease inhibitor exposures, but garlic and ginseng reduce CYP3A substrates by 44–51%. 104,105 Reductions of a similar magnitude could result in subtherapeutic boceprevir or telaprevir exposures, thus use of garlic and ginseng supplements should be avoided.…”
Section: Specific Drug Interactionsmentioning
confidence: 99%
“…Finally, a recent clinical trial showed that E. purpurea root extract did not affect the overall darunavir or ritonavir (a combination of protease inhibitors) pharmacokinetics in HIV patients [51]. Protease inhibitors are mainly metabolized by CYP3A4 and are P-glycoprotein substrates.…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%